Optimising enterprise financial sharing process using cloud computing and big data approaches. (14th July 2022) - Deng, Yimin
With the rise and application of new information technology led by big data and cloud computing, traditional enterprise financial work faces the pressure of transformation and upgrading. To improve the efficiency of enterprise management and reduce the cost of financial treatment, in this exploration, the differences, advantages and disadvantages between the traditional financial management mode and the sharing model are compared; the basic situation of Company H is analysed under the operation status of financial shared service centre. Company H's total asset exceeds 10 billion Chinese yuan, and its annual construction capacity exceeds 40 billion Chinese yuan. As its development scale continues to increase, the drawbacks of its decentralised financial management model gradually become prominent. For the problems of Company H's current financial management mode, such as high management cost, complex process, low efficiency and personnel redundancy, the solution to optimise the financial shared service centre is proposed.